Children's Character Education Values in the Qur'an (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main issue raised in this study is the values of character education of children in the Qur'an(Comparative Study of the Story of the Prophet Nuh as. with the story of Prophet Ibrahim as.). Furthermore, thissubject matter is translated into three sub-problems, namely: (1) how is the description of the value of children'scharacter education in the Qur'an which was instilled by the Prophet Nuh as. and Prophet Ibrahim as.; (2) how is thecomparison of the value of children's character education in the Qur'an which was instilled by the Prophet Nuh a.s.and Prophet Ibrahim as.; (3) how the impact of the values of children's character education instilled by the ProphetNuh as. and Prophet Ibrahim.. This research is completely classified as library research and uses a pedagogicalapproach. Sources of data were obtained from documents in the form of verses of the Qur'an and the hadiths of theProphet, interpretations, thematic interpretations, stories of the prophets, syarah hadith, and Islamic education books,children's character education books relevant to this research. The data that has been collected were analyzed usingdescriptive analysis techniques. The results showed that the Prophet Nuh as. and Prophet Ibrahim. In instilling thevalue of character education in their children, there are values of character education for children in the Qur'an. Thevalues of character education in children were instilled by the Prophet Nuh AS. namely: (1) monotheism; (2)worship; (3) morals which include: sincerity, environmental preservation on earth, independence, compassion andcare, prayer, patience, gratitude, responsibility and warning (tanzīr), respect for achievement, hard work, obedientand obedient. While the values of character education for children instilled by Prophet Ibrahim a.s. namely: (1)monotheism; (2) worship; (3) morals which include: obedient and obedient, prayer, delivery of good news (tabsyir);Optimalization has offspring, social care, patient, polite and good speaker, appreciation and achievement, safe andaway from polytheism, social care, patient, polite and good speaker, appreciation and achievement, safe and awayfrom polytheism, care and tawakkal, settlement of descendants (al-Isakān al-Żurriyah) and responsibility, gratitude,istiqamah in establishing prayer, social care, anticipation of the future, keeping promises, honest (al-Ṣiddīq);benevolent, brave, generous. This research is expected to be useful as a contribution of thought and reference in thefield of children's character education in the Qur'an, especially in imitating the Prophet Nuh as. and Prophet Ibrahim.in instilling character values in everyday life.